Immune disturbance leads to pulmonary embolism in COVID-19 more than classical risk factors: a clinical and histological study - Cicco, Sebastiano; Vacca, Antonio; Albanese, Federica; Susca, Nicola; Desantis, Vanessa; Magistro, Arianna; Cazzato, Gerardo; Cicco, Gerolamo; Sablone, Sara; Cariddi, Christel; Marozzi, Marialuisa Sveva; Catena, Cristiana; et al. (Internal and emergency medicine, 2023)
COVID-19 induces endotheliitis and one of the main complications is enhanced coagulation. The incidence of pulmonary embolism (PE) in COVID-19 (CPE) has increased and clinical features for a rigorous analysis still need to be determined. Thus, we evaluated the clinical characteristics in CPE and the immune infiltration that occurred. Between January 1 and December 31, 2021, 38 patients were affected by CPE (9 ICU, 19 males/19 females, 70.18 ± 11.24 years) out of 459 COVID-19 cases. Controls were subjects who were evaluated for PE between January 1 2015, and December 31, 2019 (92 patients, 9 ICU, 48 males/45 females, 69.55 ± 16.59 years). All patients underwent complete physical examination, pulmonary computed tomography, laboratory tests, D-dimer, and blood gas analysis. There were no differences in laboratory tests or D-dimer. In patients with CPE, pO2, alveolar–arterial oxygen difference (A-aDO2), oxygen saturation %, and the ratio between arterial partial pressure of oxygen (PaO2) and fraction of inspired oxygen (FiO2), P/F, were significantly increased. There were no differences in PaCO2. Platelet count was inversely correlated to P/F ( r = − 0.389, p = 0.02) but directly to A-aDO2 ( r = 0.699, p = 0.001) only in patients with CPE. Histology of lung biopsies (7 CPE/7 controls) of patients with CPE showed an increase in CD15 + cells, HMGB1, and extracellular MPO as a marker of NETosis, while no significant differences were found in CD3 + , CD4 + , CD8 + , and intracellular MPO. Overall, data suggest that CPE has a different clinical setting. Reduced oxygen content and saturation described in Patients with CPE should not be considered a trustworthy sign of disease. Increased A-aDO2 may indicate that CPE involves the smallest vessels as compared to classical PE. The significant difference in NETosis may suggest the mechanism related to thrombi formation.